Work, Stress, and Diurnal Bruxism: A Pilot Study among Information Technology Professionals in Bangalore City, India - S. K. Rao; M. Bhat; J. David (International Journal of Dentistry)
The study assessed the prevalence of diurnal bruxism among information technology (IT) professionals and explored plausible predictors associated with the parafunctional habit. A cross-sectional study was designed and IT professionals were invited to participate. The inclusion criteria composed of participants in service for at least one year, having natural dentition, no history of cervical or facial injury and not undergoing orthodontic therapy. The participants (N=147) were interviewed by a trained interviewer to record information. A pre-tested questionnaire that included questions related to work, stress symptoms and diurnal bruxism was completed by each participant. The prevalence of self-reported diurnal bruxism was 59%. Bivariate analyses revealed that work (𝑃<0.05) and work experience (𝑃<0.05) were significantly associated with self-reported diurnal bruxism. In the binary logistic regression analysis stress (Odds Ratio [OR] =5.9, 95% Confidence Interval [CI] 2.6–13.3) was identified to be a strong predictor of diurnal bruxism. Professionals with 11 or more years of experience were less likely to report diurnal bruxism (OR=0.04, 95% CI 0.00–0.43) than those with 1 to 5 years of work experience. The study revealed that stress and less work experience were associated with diurnal bruxism among IT professionals in Bangalore city.